2022
DOI: 10.1186/s12913-022-07491-8
|View full text |Cite
|
Sign up to set email alerts
|

Health practitioners’ perceptions of structural barriers to the identification of intimate partner abuse: a qualitative meta-synthesis

Abstract: Background Health care practitioners (HCPs) play a critical role in identifying and responding to intimate partner abuse (IPA). Despite this, studies consistently demonstrate a range of barriers that prevent HCPs from effectively identifying and responding to IPA. These barriers can occur at the individual level or at a broader systems or organisational level. In this article, we report the findings of a meta-synthesis of qualitative studies focused on HCPs’ perceptions of the structural or org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 62 publications
0
21
0
Order By: Relevance
“…The integration of an IPV response within healthcare requires establishing procedures and building specific skills (such as empathic listening, validation and assisting with referrals to other services) that may require more time than is allocated per patient [ 11 ]. It also requires a change in the institutional medical culture (from ‘treat’ to ‘care and support’) [ 10 ] and in the structural factors (from normalisation to unacceptance) [ 12 ]. Furthermore, when new programmes to improve response to VAW are implemented, it is important to first assess the readiness of the receiving health system [ 10 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The integration of an IPV response within healthcare requires establishing procedures and building specific skills (such as empathic listening, validation and assisting with referrals to other services) that may require more time than is allocated per patient [ 11 ]. It also requires a change in the institutional medical culture (from ‘treat’ to ‘care and support’) [ 10 ] and in the structural factors (from normalisation to unacceptance) [ 12 ]. Furthermore, when new programmes to improve response to VAW are implemented, it is important to first assess the readiness of the receiving health system [ 10 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similar to previous research (Sprague et al, 2014), we found that majority of women in our study contacted a healthcare professional before the violence turned physical as they were seeking help for the mental health conditions that resulted from the non‐physical violence. Research indicates a lack of adequate training and education amongst healthcare professionals to screen for IPV and refer appropriately (Al‐Natour, Qandil, & Gillespie, 2016; Hudspeth, Cameron, Baloch, Tarzia, & Hegarty, 2022; Swailes, Lehman, & McCall‐Hosenfeld, 2017). Our study builds upon this with participants reporting a lack of recognition of non‐physical forms of abuse amongst healthcare professionals, thereby leaving the women without support and at risk of further harm (Djikanovic, Celik, Simic, Matejic, & Cucic, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…depression) to take time to identify the root cause (such as IPV), and together develop an intervention or referral pathway that meets the woman's needs (Marsden, Humphreys, & Hegarty, 2021). As recognised in a meta‐synthesis, health systems require improved training, policies and referral protocols and we would highlight that the training needs to appropriately identify non‐physical IPV, intervention or referral pathways (Hudspeth et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…There are many barriers to inquiry by health practitioners and disclosure by victims/survivors 19‐21 . A systematic review of 35 quantitative studies suggested low rates of routine domestic violence screening by practitioners (with the majority reporting between 10% and 20%) 22 From meta‐syntheses of qualitative studies, we know that health practitioners experience personal and structural barriers to domestic violence inquiry and response.…”
Section: Barriers To Inquiry and Disclosurementioning
confidence: 99%
“…Personal barriers include practitioners feeling they “can’t interfere” as domestic and sexual violence are private issues, “don’t have control” over outcomes for victims/survivors, and “won’t take responsibility” as it is someone else’s role 20 . At the structural level, practitioners perceive that “the environment works against us” with lack of time and spaces, they are “trying to tackle the problem on their own” without a team behind them, and “societal beliefs enable us to blame the victim” 19 . System‐level barriers, such as the presence of the partner in consultations or a lack of training or referral services, can impede practitioners even further 23 .…”
Section: Barriers To Inquiry and Disclosurementioning
confidence: 99%